Penentuan Indeks Massa Tubuh (IMT) Melalui Pengukuran Berat dan Tinggi Badan Berbasis Aplikasi Appsheet - Sulistyo, Andhy; Resmiaini, Resmiaini (Universitas Tabanan, 2024)
Body mass index (BMI) is the most commonly used and more practical indicator to measure the level of overweight in a population, because BMI values are often associated with various medical and mental health problems. In general, the determination of BMI is done manually by measuring height and weight then doing calculations. The purpose of this research is to apply the appsheet application to record as well as provide Weight Classification information.The research location is at Darul Najah Orphanage Yogyakarta. The subjects in this study were twenty-two adolescent girls under the age of twenty years. The object of this research is height, weight and blood pressure. Data collection techniques with field observations and surveys by taking the entire population of twenty-two young women. Data analysis using the appsheet application that has been made which provides information on the Weight Classification of adolescent girls.The results of the twenty samples were five underwight, 12 normal, three over wightt and two obesity level 1. Conclusion The use of the apppshet application is very effective and efficient in providing BMI information and classifying body weight at Darul Najah Orphanage Yogyakarta. FULL TEXT PDF